Onsite Evaluation Guidelines and Procedures A Manual for Onsite Evaluators - Worthen, Blaine R.; Wasatch Inst. for Research and Evaluation, Logan, UT. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1983)
It is the purpose of this manual to present suggested steps and procedures for use by individual onsite evaluators or by the Utah State Office of Education or any other similar agency charged with responsibility for arranging or conducting onsite evaluations. Although many of the examples used in this manual are drawn from materials developed in relation to onsite evaluation of Title IV-C projects (or their earlier precursors, Title III projects), they should have broad applicability to onsite evaluation of virtually any type of educational project. Much of the material in this manual consists of simple procedures and suggestions that represent little more than "common sense"; it is in the spirit of promoting simple and straightforward approaches to onsite evaluation that this manual is offered. It is organized around the following general topics, within which specific procedures and supporting materials are discussed: Onsite Evaluation: An Effective Evaluation Strategy; Rationale for Establishing Onsite Evaluation Guidelines; Pre-visitation Considerations and Activities; Conduct of Onsite Evaluation Activities; Reporting the Results of Onsite Evaluation Visits; Evaluation of Onsite Evaluations; and Stipend and Expense Considerations. Appendixes contain evaluation materials. (BW)
Sponsoring Agency: Utah State Office of Education, Salt Lake City. Office of Curriculum and Instruction.
Administrators.
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Educational Improvement; Evaluation Criteria; Evaluation Methods; Evaluation Utilization; Evaluators; Observation; Program Evaluation; School Visitation; Onsite Evaluation; Evaluation Reports -- Site Visits; Guides, Non-Classroom.; Reports, Evaluative